The HAVCR1-centric host factor network drives Zika virus vertical transmission - Yu, Wenzhe; Tao, Jun; Cao, Hongmin; Zheng, Wanshan; Zhang, Beiang; Zhang, Yue; Xu, Peiqun; Zhang, Yiwei; Liu, Xuan; Wang, Yinan; Cai, Han; Liu, Gang; et al. (Cell reports (Cambridge), 2025)
Zika virus (ZIKV) vertical transmission results in devastating congenital malformations and pregnancy complications; however, the specific receptor and host factors facilitating ZIKV maternal-fetal transmission remain elusive. Here, we employ a genome-wide CRISPR screening and identify multiple placenta-intrinsic factors modulating ZIKV infection. Our study unveils that hepatitis A virus cellular receptor 1 (HAVCR1) serves as a primary receptor governing ZIKV entry in placental trophoblasts. The GATA3-HAVCR1 axis regulates heterogeneous cell tropism in the placenta. Notably, placenta-specific Havcr1 deletion in mice significantly impairs ZIKV transplacental transmission and associated adverse pregnancy outcomes. Mechanistically, the immunoglobulin variable-like domain of HAVCR1 binds to ZIKV via domain III of envelope protein and virion-associated phosphatidylserine. Proteomic profiling and function analyses reveal that AP2S1 cooperates with HAVCR1 for ZIKV internalization through clathrin-mediated endocytosis. Overall, our work underscores the pivotal role of HAVCR1 in mediating ZIKV vertical transmission and highlights a therapeutic target for alleviating congenital Zika syndrome. [Display omitted] •CRISPR knockout library screens placental-specific factors driving ZIKV infection•The GATA3-HAVCR1 axis dictates trophoblast lineage-specific ZIKV susceptibility•The ZIKV-E-HAVCR1-AP2S1 network regulates ZIKV entry in trophoblasts•ZIKV exploits murine Havcr1 to traverse the maternal-fetal interface Yu et al. identify host factors governing placental ZIKV infection using an unbiased CRISPR gene-knockout screen. They unravel that GATA3-hepatitis A virus cellular receptor 1 (HAVCR1)-adaptor protein 2 small σ2 (AP2S1) serves as a placenta-intrinsic regulatory axis indispensable for ZIKV entry and maternal-fetal transmission during pregnancy.